2014
DOI: 10.1021/jp504220y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Three-Dimensional Strain on Electric Conductivity in Au-Dispersed Pr1.90Ni0.71Cu0.24Ga0.05O4+δ

Abstract: The effects of tensile strain on the electronic properties of Cu- and Ga-doped Pr1.9NiO4 (PNCG) were investigated. The difference in the thermal expansion coefficient between PNCG (α = 13.5–13.9 × 10–6 K–1) and Au (α = 14.2 × 10–6 K–1) can induce tensile strain in PNCG, resulting in changes in electrical conductivity. Hall-effect measurements indicated that the tensile strain stabilized the oxidized state of PNCG, and the electrical conductivity increased because of the increased hole concentration. This sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…529 eV), which could be assigned to oxygen at interstitial sites. , A comparison of the XPS results for 0 and 1 mol % Au revealed the peak areas show that the reduced state (ca. 529 eV) of oxygen was increased by the addition of 1 mol % Au, which was correlated with an increase in interstitial oxygen (δ) of the PNCG . As shown in Figure , the peak area at ca.…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…529 eV), which could be assigned to oxygen at interstitial sites. , A comparison of the XPS results for 0 and 1 mol % Au revealed the peak areas show that the reduced state (ca. 529 eV) of oxygen was increased by the addition of 1 mol % Au, which was correlated with an increase in interstitial oxygen (δ) of the PNCG . As shown in Figure , the peak area at ca.…”
Section: Resultsmentioning
confidence: 75%
“…In the K 2 NiF 4 structure, interstitial positions in a rock salt block are considered to be fast oxide ion mobile routes because of a large free volume . In our previous work, we reported the oxygen permeation properties of PNCG with a dispersion of Au and suggested that the oxide ion conductivity increased . On the other hand, an increase in bulk oxygen dissociation and electronic density is also related with increased surface ORR because the charge transfer step is reported as the rate-determining step for oxygen dissociation on the cathode oxide .…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations